Upgrading media for the modernization of Belarusian society and international relations - Yelfimoff, Vadim A. (Journal of the Belarusian State University. Journalism, 2019)
The article is devoted to the problem of forming modern sociocultural space in aims of information society. The newest trends in globalization of security process and perspectives of pragmatic approach to them are also viewed in the article The author claims that efficiency of journalism is defined by her continuous stay on an edge of questions of the social agenda: only then journalism will be effective when it promotes making of the general route to wellbeing of society. And to creation of new effective system of the international security.